A Digital Way for Fabricating a Resin-Bonded Fixed Partial Denture Combined with Periodontal Splint in the Mandibular Anterior Region. (28th August 2022) - Shi, Xiaorui; Zhan, Yalin; Liu, Feng
Abstract : Teeth loosening are caused by insufficient supporting tissue, inflammation of periodontal tissue, or occlusal trauma, which is one of the main clinical symptoms of periodontitis. A digital technique for fabricating resin-bonded splinting fixed partial dentures (S-FPDs) is presented. It restores the missing mandible anterior teeth and splints the adjacent periodontally mobile teeth of the patient at the same time. The S-FPDs is designed and fabricated by computer-aided design and computer-aided manufacturing (CAD/CAM) technology with flexible PMMA material. The workflow is straightforward, convenient, and accurate. Meanwhile, the restoration can meet the esthetic requirements and help with the stability of adjacent loosening natural teeth spontaneously. It could be considered a medium-term provisional restorative treatment option, but further controlled investigations still be needed.